Evaluation of the Effect of Passive Cooling Techniques on Thermal Comfort Using Test Cells in the Northern Region of Brazil - Murilo Marcolini; Ricardo M. S. F. Almeida; Eva Barreira (Applied Sciences, 2022)
The high consumption of electricity in Palmas, Brazil is a direct consequence of the high temperatures identified throughout the year. Therefore, it is necessary to search for sustainable technologies that contribute to comfort through passive cooling, thus reducing the energy consumption. This work presents the results of an experimental campaign of 11 months, in which the effects of shading devices, the use of a low-emissivity reflective film, the implementation of natural ventilation and the application of reflective painting are evaluated, when applied individually and combined. The results show that when applied individually, natural cross ventilation was the most effective at night, while reflective painting showed better performance during the day. Regarding the combinations of techniques, the best combination occurred when reflective painting was used together with natural ventilation, and the result was a relevant improvement in the performance, ensuring high temperature reductions when compared to the control.